Implementasi Project Based Learning Menggunakan Barang Bekas Untuk Meningkatkan Hasil Belajar dan Sikap Gotong Royong Pada Pelajaran Pendidikan Agama Kristen Kelas 5 SD Kristen Imanuel Semarang - Joan Silva Setyowati; Karnawati; Tjie Fu Sien (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This study examines the learning process of Christian Religious Education for Grade 5 at Immanuel Christian Elementary School in Semarang, which faces challenges such as students scoring below the school’s Minimum Competency Criteria (KKM) of 75, inadequate learning facilities, low student collaboration skills, the dominance of lecture methods, and the absence of teaching modules and visual aids. The research utilized a qualitative descriptive method with a classroom action research approach developed by Kemmis and McTaggart (1998), conducted during the 2023-2024 academic year. The study consisted of two cycles. In the Pre-Cycle phase, 8 out of 18 students scored below the KKM. In Cycle 1, the students’ average scores improved, with three students still below the KKM, and significant improvements were observed in lesson preparation. Cycle 2 showed further progress, with pre-test results reaching 70% and post-test results achieving 90%. Students' teamwork attitudes improved from 62.2% in Cycle 1 to 83.3% in Cycle 2, with enhancements in aspects such as cooperation, communication, adaptability, and responsibility. The Project-Based Learning (PjBL) approach received positive feedback from students, teachers, and parents. The use of recycled materials made the content more engaging and memorable for students. It can be concluded that PjBL is effective in improving learning outcomes and teamwork attitudes in Christian Religious Education. Recommendations include improving learning facilities, such as access to the internet, libraries, and laboratories; encouraging innovative teaching strategies; and conducting further research on the application of PjBL in other subjects or schools with different characteristics, as well as exploring the role of technology in supporting PjBL.